PEDAGOGICAL AND PSYCHOLOGICAL ASPECTS OF ENSURING SAFE INCLUSIVE EDUCATIONAL CONTINUITY - Kobilova Shaxnoza Xudayshukurovna (Bright Mind Publishing, 2025)
This article analyzes the importance of ensuring the safety of students studying in inclusive education, the active implementation of inclusive education in general education schools, the organization of educational activities for children with special educational needs together with their normally developing peers, and the fact that inclusive education is an educational environment that reveals the special educational needs and individual capabilities of students with disabilities. Ensuring the continuity of inclusive education requires a comprehensive understanding of the pedagogical and psychological factors that affect the educational process of students with diverse needs. The results show that ensuring the continuity of inclusive education in Uzbekistan requires a multifaceted approach that includes policy implementation, teacher training, integration of assistive technologies, and broader awareness in society.
Keywords: Inclusive education, student with disabilities, educational needs, individual opportunities, educational environment, school, coordinated counseling, psychologist, medical worker, pedagogue, defectologist, inclusive education, pedagogical factors, psychological adaptation, special educational needs, teacher training, continuity of education, accessibility, assistive technology, social inclusion.